A crashing-based time-cost trade-off model considering quality cost and contract clauses. Issue 6 (24th June 2021) - Akin, Firat Dogu; Polat, Gul; Turkoglu, Harun; Damci, Atilla
Abstract: The success of a construction project is often evaluated by time, cost, and quality performances, which are interdependent. Shortening the project duration does not only increase the direct cost but also affects the project's quality cost positively or negatively. In addition, the contract clauses in terms of penalty cost and early finish bonus have a significant impact on project duration and cost. This study proposes a crashing-based model, which simultaneously considers quality cost and contract clauses, to solve time-cost trade-off problems. The applicability of the proposed model is demonstrated with an illustrative example. The results of the proposed model were also compared with the results of two meta-heuristic algorithms, namely Particle Swarm Optimization (PSO) and Genetic Algorithm (GA), in order to validate the effectiveness of the model. The results revealed that the proposed model provides better solutions than these algorithms in terms of total project cost corresponding to different durations.